New records of Haplaxius (Hemiptera: Cixiidae) in the Dominican Republic,with description of a new species - Ferreira, Mileida; Mckamey, Stuart H.; Martinez, Reina T. (Zootaxa, 2010)
The planthopper genus Haplaxius Fowler has a New World distribution. Kramer (1979) revised the New World Myndus Stål, consisting of 63 species. In that revision, Kramer synonymized Haplaxius and Paramyndus Fennah under Myndus, and P. cocois Fennah (1945), the type species of Myndus, as a junior synonym of M. crudus. Emeljanov (1989) reinstated the genus Haplaxius Fowler for the New World species formerly in Myndus. These consequent name changes have been accepted by all subsequent taxonomists (e.g., see Holzinger et al. 2002) but use of the name Myndus, when referring to New World species is still widely used, erroneously, in the applied literature.